STRUKTUR BAWAH PERMUKAAN DAERAH SEMARANG DAN SEKITARNYA DARI METODE GAYA BERAT DAN MAGNET - Nainggolan, D.A (Pusat Survei Geologi, 2008)
The result of gravity measurements in the studied area, which is mainly covered by volcanic rocks, have an anomaly valueranging from-13 to 44 mgal. Geologic and tectonical development of the area may still be active until recently(?). For this reason, The Geological Survey Institute conducted detailed gravity study to delineate this possibility moreaccurately. The hydrocarbon reserve had ever been exploitated by the Dutch Government from the Cipluk field, southern of Kendal city and already been closed in 1930.From this fact, other areas In the northen part of this Quadrangle is potential for the hydrocarbon resource. The southern part of Ungaran Mountain may also potensial for the geothermal resource. The qualitative analysis of the anomaly patterns, subsurface profile models including the geological structures reflects the geological processes, tectonics and Its relationship with natural resources. The qualitative analysis on residual and Bouguer anomalies indicates that the structures in the study area have mainly east –west and north south directions. Keywords: gravity, magnet, Bouguer anomaly,structures,Semarang